1986 y-Walk participants socializing - Brock, Trish (photographer):::Creator::::::::::::
Negative shows a group of men and women who are participants in the 1986 y-Walk. They are socializing in a room with balloons. Some of the balloons have floated to the ceiling and some are probably being held by people in the crowd.